2015
DOI: 10.1093/jnci/djv155
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of the Lack of Angiogenesis in the Formation of Lymph Node Metastases

Abstract: We provide preclinical and clinical evidence that sprouting angiogenesis does not occur during the growth of lymph node metastases, and thus reveals a new mechanism of treatment resistance to antiangiogenic therapy in adjuvant settings. The targets of clinically approved angiogenesis inhibitors are not active during early cancer progression in the lymph node, suggesting that inhibitors of sprouting angiogenesis as a class will not be effective in treating lymph node metastases.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

8
125
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 108 publications
(133 citation statements)
references
References 51 publications
8
125
0
Order By: Relevance
“…As metastatic lesions grow, the surface area of the blood vessels becomes limiting, causing the distribution of cancer cells to revert to that of a random distribution. This phenotype is consistent with the lack of sprouting angiogenesis in lymph node metastases (25). In lymph nodes with large lesions, 1%±0.5% of cancer cells were found in blood vessels (Fig.…”
supporting
confidence: 86%
“…As metastatic lesions grow, the surface area of the blood vessels becomes limiting, causing the distribution of cancer cells to revert to that of a random distribution. This phenotype is consistent with the lack of sprouting angiogenesis in lymph node metastases (25). In lymph nodes with large lesions, 1%±0.5% of cancer cells were found in blood vessels (Fig.…”
supporting
confidence: 86%
“…3, bottom right). In this context, our results also offer a potential explanation for the failure of antiangiogenesis therapy postoperatively (2), because micrometastatic lesions might have very low MVD and lack angiogenesis (28). Additionally, a significant fraction of BCs are desmoplastic (29,30), which might cause vessel compression and reduce the patency of vessels (31)(32)(33).…”
Section: Low Vascularity Poorly Perfusedmentioning
confidence: 80%
“…By contrast, they were mainly characterized by bulky nodal disease, pointing towards tumors with a predisposition to lymphatic spread, and a relative inability for hematogenous spread. Lymphatic spread is unique, as neovascularization is not an essential prerequisite (11). It was recently demonstrated that, compared with hematogenous spread, lymphatic spread is independent of epithelial-to-mesenchymal transition (EMT) in the primary tumor (12).…”
Section: Discussionmentioning
confidence: 99%